"I'm Always in This Conflict" – Students' Struggle of Plurilingual Identity Expression, Linguistic Insecurity, and Assimilation in Switzerland's Higher Education. Issue 1 (2nd January 2021) - Becker, Anna
Abstract: This article examines the connection among university students' lived experiences of language, ideologies, and linguistic repertoires through visual and verbal representations. It demonstrates that linguistic repertoires are crucial for students' identities, yet impeded by restricting, homogenizing policies, which reproduce the "monolingual habitus" even in officially multilingual contexts. It advocates multilingualism in Switzerland's higher education to increase inclusive and equitable learning opportunities while addressing ideologies and their implications for students' identities and academic trajectories.